Relationship between software management and human resource management - Almarrani, Ehab Yahya Yahya (Journal of Applied Technology and Innovation, 2021)
Software management has greatly impacted organizations and Human Resource Management (HRM) is no exception. In this context, software management is often introduced with the rationale that it could offer benefits such as cost reduction, time savings, and strategic transformation. Many organizations have invested in HRM systems in the hope of transforming the Human Resource department (HR) into a strategically. Extant research, however, shows that many organizations fail to achieve intended effects from their software management investments and as result beliefs around the strategic value of HRM vary. This thesis aims to critically examine the link between HRM investments and strategic value. The review focused on perceptions about HRM systems within organizations and sought to unearth how perceptions shape the route of software management implementation towards a strategy outcome. Our findings indicate that the majority of the studies are not guided by a leading theoretical paradigm. Furthermore, strategic barriers such as implementation problems and limited use of the system that does not reflect its potential are identified and discussed. By examining some common factors that have been identified to shape the translation of HRM systems from initial perception to actualized use we lay the foundation for more nuanced theorizing of HRM use within contemporary organizations.